(3/15-x)×1/3=2/5
Giúp mình với !
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`2x-15=-25`
`2x=-10`
`x=-5`
___________
`3/5<x/10<4/5`
`3/5=(3xx10)/(5xx10)=30/50`
`x/10=(5x)/(10xx5)=(5x)/50`
`4/5=(4xx10)/(5xx10)=40/50`
`=>30/50<(5x)/50<40/50`
`=>30<5x<40`
`=>x=7`
Giải:
a) \(2\dfrac{17}{20}-1\dfrac{15}{11}+6\dfrac{9}{20}:3\)
\(=\dfrac{57}{20}-\dfrac{26}{11}+\dfrac{129}{20}:3\)
\(=\dfrac{107}{220}+\dfrac{43}{20}\)
\(=\dfrac{29}{11}\)
b) \(4\dfrac{3}{7}:\left(\dfrac{7}{5}.4\dfrac{3}{7}\right)\)
\(=\dfrac{31}{7}:\left(\dfrac{7}{5}.\dfrac{31}{7}\right)\)
\(=\dfrac{31}{7}:\dfrac{31}{5}\)
\(=\dfrac{5}{7}\)
c) \(\left(3\dfrac{2}{9}.\dfrac{15}{23}.1\dfrac{7}{29}\right):\dfrac{5}{23}\)
\(=\left(\dfrac{29}{9}.\dfrac{15}{23}.\dfrac{36}{29}\right):\dfrac{5}{23}\)
\(=\dfrac{60}{23}:\dfrac{5}{23}\)
\(=12\)
Bài 7:
a, \(x\) = \(\dfrac{1}{5}\) + \(\dfrac{2}{11}\)
\(x\) = \(\dfrac{11}{55}\) + \(\dfrac{10}{55}\)
\(x=\dfrac{21}{55}\)
b, \(\dfrac{x}{15}\) = \(\dfrac{3}{5}\) - \(\dfrac{2}{3}\)
\(\dfrac{x}{15}\) = \(\dfrac{9}{15}\) - \(\dfrac{10}{15}\)
\(\dfrac{x}{15}\) = \(\dfrac{1}{15}\)
\(x\) = 1
c, \(\dfrac{11}{8}\) + \(\dfrac{13}{6}\)= \(\dfrac{85}{x}\)
\(\dfrac{33}{24}\) + \(\dfrac{52}{24}\) = \(\dfrac{85}{x}\)
\(\dfrac{85}{24}\) = \(\dfrac{85}{x}\)
24 = \(x\)
Bài 1:
a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)
\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)
\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)
\(\Rightarrow x=\dfrac{1}{6}\)
A= 2/5 - 1
= -3/5
B= -30/24 + 4/24 - 36/24
= 31/12
A = 3/7 x 2x7/3x5 - 3x6/7x3 x 7/6 = 2/5 - 3/3 = 2/5 - 5/5 = -3/5
B=1/6 - (5/4 + 3/2) = 1/6 -(5/4 + 6/4)= 1/6 - 11/4 = 2/12 - 33/12 = - 21/12
a) ( x - 1 )( x2 + x + 1 ) + x( x + 2 )( 2 - x ) = 5
<=> x3 - 1 - x( x + 2 )( x - 2 ) = 5
<=> x3 - 1 - x( x2 - 4 ) = 5
<=> x3 - 1 - x3 + 4x = 5
<=> 4x - 1 = 5
<=> 4x = 6
<=> x = 6/4 = 3/2
b) 5x( x - 3 )2 - 5( x - 1 )3 + 15( x + 4 )( x - 4 ) = 5
<=> 5x( x2 - 6x + 9 ) - 5( x3 - 3x2 + 3x - 1 ) + 15( x2 - 16 ) = 5
<=> 5x3 - 30x2 + 45x - 5x3 + 15x2 - 15x + 5 + 15x2 - 240 = 5
<=> 30x - 235 = 5
<=> 30x = 240
<=> x = 8
a,\(\left(x-1\right)\left(x^2+x+1\right)+x\left(x+2\right)\left(2-x\right)=5\)
\(< =>x^3-1+x\left(4-x^2\right)=5\)
\(< =>x^3-1+4x-x^3=5\)
\(< =>4x-1-5=0< =>4x-6=0< =>x=\frac{3}{2}\)
b, \(5x\left(x-3\right)^2-5\left(x-1\right)^3+15\left(x+4\right)\left(x-4\right)=5\)
\(< =>5x\left(x^2-6x+9\right)-5\left(x^3-3x^2+3x-1\right)+15\left(x^2-16\right)=5\)
\(< =>5x^3-30x^2+45x-5x^3+15x^2-15x+5+15x^2-240=5\)
\(< =>\left(5x^3-5x^3\right)+\left(15x^2+15x^2-30x^2\right)+\left(45x-15x\right)+5-240=5\)
\(< =>30x-240=5-5=0< =>x=\frac{24}{3}=8\)
ĐKXĐ: \(-5\le x\le3\)
Đặt \(\sqrt{x+5}+\sqrt{3-x}=t>0\Rightarrow t^2=8+2\sqrt{-x^2-2x+15}\)
\(\Rightarrow-2\sqrt{-x^2-2x+15}=8-t^2\) (1)
Pt trở thành:
\(t+8-t^2-2=0\Leftrightarrow-t^2+t+6=0\Rightarrow\left[{}\begin{matrix}t=3\\t=-2\left(loại\right)\end{matrix}\right.\)
Thế vào (1): \(-2\sqrt{-x^2-2x+15}=-1\)
\(\Leftrightarrow\sqrt{-x^2-2x+15}=\dfrac{1}{2}\)
\(\Leftrightarrow-x^2-2x+15=\dfrac{1}{4}\)
\(\Leftrightarrow...\)